Response mechanisms of sugarcane seedlings to the allelopathic effects of root aqueous extracts from sugarcane ratoons of different ages - Wang, Xiaoming; Wang, Shilong; Zhu, Jinghuan; Zuo, Linzhi; Yang, Zuli; Li, Lei (Frontiers in Plant Science, 2022)
Sugarcane ratoon performance declines with increasing age due to the intergenerational accumulation and release of allelochemicals by old sugarcane roots. We aimed to clarify the effects of these allelochemicals on sugarcane seedling growth under continuous sugarcane ratoon cropping. We investigated the allelopathic effects of treatment with root aqueous extracts from sugarcane ratoons of different ages on the osmoregulatory substance content, antioxidant enzyme activity, membrane lipid peroxidation product content, photosynthetic physiological characteristics, and root exudate enzymatic characteristics of sugarcane seedlings. The root aqueous extracts exerted allelopathic effects on sugarcane seedlings. The electrolyte permeability, proline content, soluble protein content, soluble sugar content, malondialdehyde content, and catalase activity of the leaves were more sensitive than those of the roots. Conversely, the superoxide dismutase and peroxidase activities of the roots (positive response) were more sensitive than those of the leaves (negative response). The total chlorophyll content and net photosynthetic rate of the leaves exhibited relatively sensitive negative responses. Urease activity negatively responded but sucrase activity positively responded. We concluded that the root aqueous extracts of sugarcane ratoons may exert their allelopathic effects by affecting the level of osmoregulatory substances and causing peroxidative damage to the cell membranes of sugarcane seedlings and altering the activities of various enzymes in the rhizosphere.